Who Killed New York City? Imagination, Authenticity, and Violence in City Souvenirs - Jones, Ryan Christopher (Lidé města, 2021)
Despite decreasing crime numbers over the last 30 years, for some, New York City still has a reputation as an inherently violent city. In various souvenir shops across the city, select souvenirs indulge in this reputation by depicting New York City as a place where grittiness, violence, and crime are essential to the experience of “real” New York. This essay meditates on the implications of such souvenirs, as they play on the fears, desires, and imagination of travellers. To illustrate these points, I use a series of black-and-white photos made in December 2020 depicting scenes from a cluster of souvenir shops in Lower Manhattan.